PWE-277 Fracture prevalence and vitamin D status in primary biliary cirrhosis: the Leicestershire experience. (28th May 2012) - Krishnamoorthy, R; Grant, A; Sheldon, P; Delahooke, T
Abstract : Introduction: Metabolic bone disease is a recognised complication in Primary Biliary Cirrhosis (PBC) and increases the risk of developing fractures. Although osteoporosis is the major contributor, Vitamin D (25- hydroxy- vitamin- D3) deficiency due to fat-soluble vitamin malabsorption is also a contributing factor for bone disease in PBC. Our objective was to assess the prevalence of fractures and vitamin D deficiency in PBC patients. Methods: Patients with diagnosed with PBC between the years 1994 and 2011 were retrospectively identified from the hepatology outpatients. Fracture data were collected from the x-ray reports in the radiology software. Biochemical data including AMA titres and Vitamin D status were retrospectively identified and entered using the pathology database. The grading for Vitamin D levels were as follows: severely deficient- 20 mg/l or >50 nmol/l. Available Bone Mineral Density (BMD) data in patients who had a Dual-emission x-ray absorptiometry (DEXA) scan was studied. Results: Among 209 patients (179 female, median age 68 years, 168 AMA positive with median AMA titre of 1 in 256) with PBC, 27 patients (12.9%, 25 females, median age 74) had sustained a fracture during their clinical course. 33 fracture episodes were identified. Femur/hip fractures were the commonest (9/33, 27%), followed by hand (5/33, 15%). DEXA scans were performed in 39 patients, with a median T score of −2.2. Vitamin D levels were available in 91 patients (44%), the levels being adequate in only 27 patients (29.6%), reflecting the magnitude of the Vitamin D status. 38 patients were insufficient (41.7%), 17 were deficient (18.6%) and 9 were severely deficient (0.09%). Conclusion: Fracture prevalence and vitamin D deficiency is high in PBC patients. Assessing Vitamin D status is a useful measure to improve bone health and reduce the burden of metabolic bone disease. Competing interests: None declared. Reference: 1. Solaymani-Dodaran M, Card TR, Aithal GP, et al. Fracture risk in people with primary biliary cirrhosis: a population-based cohort study. Gastroenterology 2006;131 :1752.